Ocean-Atmosphere Interactions of Gases and Particles. - Liss, Peter S. (Springer Earth System Sciences Series, 2014)
This book examines how gases and particles formed in the oceans affect the chemistry and physics of the atmosphere when they move from ocean to atmosphere. It also details how material deposited from the atmosphere affects the biogeochemistry of the oceans.